A Study of Social Interaction Between Principals and Teachers in Building an Inclusive Organizational Climate - Andi Muhlis; Muh. Tahir Malik; Ali Hanafi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to analyze the social interaction patterns of the principal and teachers, understand the application of inclusive values ​​in school social interactions, and identify structural and cultural barriers in building an inclusive organizational climate at the UPT SDN Kohala No. 10 Selayar Islands. This study uses a qualitative research type with a phenomenological approach. The research location was carried out at the UPT SDN Kohala No. 10 Selayar Islands for six months. The main informant of the study was the principal, while key informants consisted of several teachers who actively interacted in the school organization. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data analysis used the Miles and Huberman model through data reduction, data presentation, and drawing conclusions. Data validity tests were carried out using triangulation of sources, techniques, and time. The results of the study indicate that the social interaction patterns between the principal and teachers develop through open two-way communication, collective work coordination, and social relationships built in an atmosphere of family and mutual trust. Inclusive values ​​are understood as attitudes of equality, openness, respect, and togetherness that are applied in the daily life of the school organization. The obstacles found consisted of structural obstacles in the form of time constraints, workload, geographical conditions of the islands, and limited facilities, as well as cultural obstacles in the form of seniority, feelings of embarrassment, and potential communication misunderstandings.